Genome-Wide Analysis of Protein-Coding Variants in Leprosy - Liu, Hong; Wang, Zhenzhen; Li, Yi; Yu, Gongqi; Fu, Xi’an; Wang, Chuan; Liu, Wenting; Yu, Yongxiang; Bao, Fangfang; Irwanto, Astrid; Liu, Jian; Chu, Tongsheng; et al. (Journal of investigative dermatology, 2017)
Although genome-wide association studies have greatly advanced our understanding of the contribution of common noncoding variants to leprosy susceptibility, protein-coding variants have not been systematically investigated. We carried out a three-stage genome-wide association study of protein-coding variants in Han Chinese, of whom were 7,048 leprosy patients and 14,398 were healthy control subjects. Seven coding variants of exome-wide significance were discovered, including two rare variants: rs145562243 in NCKIPSD (P = 1.71 × 10–9, odds ratio [OR] = 4.35) and rs149308743 in CARD9 (P = 2.09 × 10–8, OR = 4.75); three low-frequency variants: rs76418789 in IL23R (P = 1.03 × 10–10, OR = 1.36), rs146466242 in FLG (P = 3.39 × 10–12, OR = 1.45), and rs55882956 in TYK2 (P = 1.04 × 10–6, OR = 1.30); and two common variants: rs780668 in SLC29A3 (P = 2.17 × 10–9, OR = 1.14) and rs181206 in IL27 (P = 1.08 × 10–7, OR = 0.83). Discovered protein-coding variants, particularly low-frequency and rare ones, showed involvement of skin barrier and endocytosis/phagocytosis/autophagy, in addition to known innate and adaptive immunity, in the pathogenesis of leprosy, highlighting the merits of protein-coding variant studies for complex diseases.